2013
DOI: 10.1177/1741143213499262
|View full text |Cite
|
Sign up to set email alerts
|

What matters to principals when they evaluate teachers? Evidence from Cyprus

Abstract: Teacher evaluation conducted by school principals is a common worldwide practice. However, there are many reservations about principals' ability to evaluate teachers reliably. Reservations appearing in the literature include inflated ratings, minimal discrimination of teacher quality, and evaluations influenced by factors irrelevant to teacher effectiveness. This article examines whether principals can distinguish effective and ineffective teachers and whether principals can identify the teacher, principal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(43 reference statements)
3
9
0
1
Order By: Relevance
“…The OECD findings have been confirmed by other independent academic research, which has found that teacher evaluation by school principals is one of the most widespread types of teacher evaluation worldwide (Brandt et al, 2007;Orphanos, 2014), but at the same time, the researchers have warned that teacher evaluation by school principals might be inflated or lack accuracy (Orphanos, 2014). The argument regarding school principals' inaccuracy might be further worsened in the PISA data since the data collected on TMMs are reported by school principals, and it can be claimed that if teachers themselves reported the data on how their teaching practices are monitored, different results could be obtained from those reported by principals.…”
Section: Conceptual Framework and Literature Reviewsupporting
confidence: 54%
“…The OECD findings have been confirmed by other independent academic research, which has found that teacher evaluation by school principals is one of the most widespread types of teacher evaluation worldwide (Brandt et al, 2007;Orphanos, 2014), but at the same time, the researchers have warned that teacher evaluation by school principals might be inflated or lack accuracy (Orphanos, 2014). The argument regarding school principals' inaccuracy might be further worsened in the PISA data since the data collected on TMMs are reported by school principals, and it can be claimed that if teachers themselves reported the data on how their teaching practices are monitored, different results could be obtained from those reported by principals.…”
Section: Conceptual Framework and Literature Reviewsupporting
confidence: 54%
“…What extent the association between principal effectiveness and teacher turnover differs for highperforming and low-performing teachers, and, furthermore, whether these associations vary by different measures of teacher performance?" (Grissom & Bartanen, 2018) ▪ How school principals consider effective and ineffective teachers is dedicated in 7 studies (Donaldson & Mavrogordato, 2018;Harris, Ingle, & Rutledge, 2014;Maharay, 2014;Master, 2014;Orphanos, 2014;Range, Hewitt, & Young, 2014;Wind et al, 2019). There are examples of the following research questions:…”
Section: Objectives and Research Questions Of Studiesmentioning
confidence: 99%
“…What principal characteristics and practices influence evaluations of teacher effectiveness?" (Orphanos, 2014) ▪ "How school leaders use high-stakes teacher evaluation to improve and, if necessary, remove low-performing teachers in their schools? How cognitive, relational and organizational factors play a role in shaping the way school leaders implement teacher evaluation?"…”
Section: Objectives and Research Questions Of Studiesmentioning
confidence: 99%
“…Principals are in a good position to evaluate teachers, because they interact with them on a daily basis and own information on their work (Orphanos, 2014). However, conducting teacher appraisal is not the sole responsibility of school principals and administrators; it is important that teachers and other concerned parties be involved in the development and implementation of teacher appraisal schemes (Peterson, 2000; Robles, 2007; Stiggins and Duke, 1988; Stronge and Tucker, 2003), as this increases all parties’ understanding and ownership of teacher appraisal.…”
Section: Literature Reviewmentioning
confidence: 99%